Comparing the Effects of Animated Films and Posters on the Religious and Moral Development of Children Aged 5–6 Years - Azmatul Kholilah; Zaini Dahlan; Ahmad Syukri Sitorus (TEMATIK: Jurnal Pemikiran dan Penelitian Pendidikan Anak Usia Dini, 2026)
This study aims to examine and compare the influence of animated films and poster media on the religious and moral development of children aged 5–6 years at RA Permata. This research was motivated by the need for engaging and developmentally appropriate learning media to support children’s internalization of religious and moral values. A quantitative approach with a two-group pretest-posttest experimental design was employed. The sample consisted of 40 children selected from a population of 45 children using Slovin’s formula and divided into an experimental group using animated films and a control group using poster media. Data were collected through structured observation, questionnaires, and documentation, and analysed using the Wilcoxon Signed Rank Test and Mann-Whitney U Test. The results showed that both animated films and poster media had a significant effect on children’s religious and moral development (p < 0.001). The Mann-Whitney U Test also showed a significant difference between the two media (p = 0.038), with animated films obtaining a higher mean rank (24.30) than posters (16.70). These findings indicate that animated films are more effective in stimulating children’s religious and moral development.